Tempat Sampah Pintar Berbasis Internet of Things di Pesantren Terpadu Ulul Abshor Semarang - Duta, Iman Surya; Priyadi Priyadi; Supriadi, Candra (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2026)
The development of information technology drives the need for digital literacy within Islamic boarding schools or pesantren. Observations at Pesantren Terpadu Ulul Abshor indicate low understanding of the Internet of Things (IoT) and poor waste management that risks disrupting health. This study aims to develop an IoT-based smart trash can using a Wemos D1 Mini micro-controller, ultrasonic sensor, PIR sensor, servo motor, LED indicator, buzzer, and the Blynk application for remote monitoring via smartphone. The Research and Development or R&D method was applied through the stages of design, implementation, and structured testing. The test results show that the entire system functions successfully. The PIR sensor detects human presence, the ultrasonic sensor measures waste capacity accurately, the servo opens and closes automatically, and the Wemos D1 Mini successfully sends full-condition notifications upon reaching 80 percent capacity to the petugas Blynk application. The feasibility test by internal and external validators yielded a total score of 34, placing it in the very good category. This research is beneficial for improving sanitation efficiency while serving as a practical learning medium for IoT technology among students.